Diversity of strength training methods: A theoretical approach - Lin, J.; Chen, T. (Strength and Conditioning Journal, 2012)
The most known methods for strength training revolve around muscle hypertrophy, which can effectively increase muscle mass. In theory, a method focusing on anatomical adaptation may build a strong musculoskeletal structure by strengthening connective tissues and muscles required for supporting, balancing, and stabilizing the body. Strength training through the use of heavy loads increases the number of motor units recruited. Explosive movements may familiarize the neuromuscular system and enhance the efficiency of the activation frequency. This article will explore various training methods in theory to maximize athletic performance.